Structure and assembly process of fungal communities in the Yangtze River Estuary - Qu, Wu; Zuo, Yaqiang; Zhang, Yixuan; Wang, Jianxin (Frontiers in Microbiology, 2024)
Marine fungi are essential for the ecological function of estuarine ecosystems. However, limited studies have reported on the structure and assembly pattern of the fungal communities in estuaries.The purpose of this paper is to reveal the structure and the ecological process of the fungal community in the Yangtze River Estuary (YRE) by using the amplicon sequencing method. Phyla of Ascomycota, Basidiomycota, and Chytridiomycota were dominant in the seawater and sediment samples from YRE.The null model analysis, community neutral community model (NCM), and phylogenetic normalized stochasticity ratio (pNST) showed that the stochastic process dominated the assembly of fungal communities in YRE. Drift and homogeneous dispersal were the predominant stochastic processes for the fungal community assembly in seawater and sediment samples, respectively. Co-occurrence network analysis showed that fungal communities were more complex and closely connected in the sediment than in the seawater. Phyla Ascomycota, Basidiomycota, and Mucoromycota were the potential keystone taxa in the network. These findings demonstrated the importance of stochastic processes for the fungal community assembly and showed the crucial taxa for monitoring the health of YRE fungal communities, thereby widening our knowledge of the community structure and dynamics of fungi for the future management, utilizationstudy and utilization in YRE ecosystem.